A Review of Important Activities and Studies - Planning Commission (Planning Commission, 1969)
The review of important activities and studies for 1969–70 provides a detailed account of the multifaceted efforts undertaken by the Planning Commission in finalising and operationalising the Fourth Five-Year Plan (1969–74) and the Annual Plan for 1970–71 within the broader framework of India’s development strategy. It outlines the extensive consultative process involving the National Development Council, Parliament, State Governments, financial institutions, and various stakeholders to refine plan priorities, resource allocation, and policy directions. Emphasis was placed on enhancing agricultural productivity, irrigation, power, rural electrification, and industrial growth, supported by improved financial resource mobilisation through taxation reforms, institutional financing, and the impact of bank nationalisation. The report highlights innovations in planning methodology, including more detailed and operational annual plans with defined targets, timelines, and monitoring mechanisms. It also underscores the importance of perspective planning through long-term projections of growth, sectoral output, investment, and balance of payments, ensuring consistency and sustainability in development objectives. Significant analytical work was conducted on economic trends, savings and investment patterns, and trade and aid relationships. Additionally, the Commission undertook extensive studies on natural resources, particularly forest and mineral resources, focusing on their conservation, utilisation, and role in industrial development. Overall, the review reflects a comprehensive, data-driven, and participatory approach to national planning aimed at achieving balanced economic growth, self-reliance, and efficient utilisation of resources.
Government of India, Planning Commission
Government of India, Planning Commission
Keywords: Fourth Five-Year Plan, Annual Plan 1970-71, Planning Commission Activities, Resource Mobilisation, Economic Policy Review, Perspective Planning, Financial Resource Assessment, Agricultural and Industrial Development, Natural Resource Studies, Forest and Mineral Resources, Infrastructure and Energy Planning, Public Sector Investment